Parental predictors of childhood vaccination adherence in border areas of Southern Vietnam: a first look at minority communities - An Dai Tran; Charuai Suwanbamrung; Muhammad Haroon Stanikzai; Nirachon Chutipattana; Shamarina Shohaimin; Patthanasak Khammaneechan; Le Minh Luan; Tran Phu Dien; Truong Thanh Nam; Phan Thanh Tung; Cua Ngoc Le (Jornal de Pediatria, 2025)
Objectives: Suboptimal timeliness and coverage of childhood vaccination programs undermined their effectiveness in achieving population-level immunity. This issue is particularly concerning among minority populations, where disparities in vaccination adherence persist. To address this gap, the study assessed the extent of parental adherence to age-appropriate childhood vaccination and its predictors among the minority children under five years of age. Methods: This cross-sectional study was conducted in three districts of Dong Thap Province, Vietnam, and neighboring Cambodia. A total of 449 ethnic minority parents with children under five years old participated. Data were gathered through face-to-face household interviews using a structured questionnaire, complemented by direct observation of the children’s vaccination cards to verify adherence. Binary logistic regression was used to identify predictors of vaccination adherence. Results: The adherence rate to childhood vaccination among children in the minority population was 18.9 %. Parental adherence was significantly higher for children under one year of age (aOR = 2.54, 95 % CI: 1.29–5.03) and for firstborn children (aOR = 3.48, 95 % CI: 1.36–9.92). Within the Health Belief Model framework, greater perceived barriers were associated with lower adherence (aOR = 0.32, 95 % CI: 0.21–0.49), while higher parental self-efficacy was linked to increased adherence (aOR = 1.84, 95 % CI: 1.11–3.11). Conclusion: This study revealed a low parental adherence rate (18.9 %) to childhood vaccination. A child’s age, birth order, perceived barriers, and parental self-efficacy influenced adherence. These findings emphasize the need to incorporate these factors into targeted policies and interventions for improving immunization rates in minority populations and comparable settings.